Optimasi Desain Pembangkit Listrik Kapasitas 200 kW Menggunakan Tenaga Matahari dengan Sistem Pumped Storage - Iwan Pramono; As Natio Lasman (Magister Teknik Mesin Universitas Pancasila, 2020)
This research was conducted by analyzing and optimizing the design of solar power plants with pumped storage systems as a source of renewable energy for remote areas in Indonesia. This research is very important to be done to solve the problem of meeting the electricity needs, especially in remote areas. The scheme is implementing 5 options in the pumped storage system. The system design is calculated and analyzed then optimization is done using Ansys fluent software. After that, all options are analyzed and compared in terms of economics related to Life-Cycle Cost (LCC) and Break Event Point (BEP) to get the best scheme. It was found that option A is better than other options in terms of system implementation because it requires the smallest number of pumps. From an economic standpoint, the LCC for option A is 63% lower than option C and higher than option B, D and E which are 2%, 5% and 25%, respectively. The lowest LCC is obtained by option E but has its own challenges in its application because it requires 540 pumps. The fastest BEP is obtained by option A with 9.47 years followed by an option D with 9.6 years. The longest BEP with 12.74 years was obtained by an Option C. Therefore, the use of pumped storage systems in solar power plants as an alternative renewable energy provides opportunities that are technically very possible and have the potential for continuous power supply in remote areas.